BBS First Year Students' Expectations in Learning English - Neupane, Umapati (Vox Batauli, 2023)
This research paper article aims at identifying and analyzing BBS first year students' expectations in learning English (foreign language). The researcher assumes that foreign language learners have expectation in learning English. Such expectations have a great influence in the learners’ learning goals as well as motivation. Apart from this, it aims to find out the students' attitude towards learning English. The present study was conducted on 54 students of BBS I years students selected randomly from constituent affiliated campus of TU in Rupandehi district. The study sets out to investigate the expectations that BBS first year students have for learning English as a foreign language in context of Nepal. Many of the learners study foreign language mainly for jobs either in the native country or in the foreign countries. The researcher wants to find out the reason for migrating in the foreign countries. Many students are migrating to the foreign countries after studying business English to get jobs. The reason of this massive migrating to the foreign countries is to get jobs which they think to get after studying business English so that they can be able to deal with foreigners effectively. As a result, the country is facing brain drain problem. The results that the study revealed have thematically been grouped and presented under five broad headings. Normally, English for employability, internal and external business communication and diplomatic relation, academic success, self improvement and social status and professional skills. This article depicts learner's expectation in learning second language. Moreover, this research article presents some future directions for further investigations in the area.